The effect of physical activity in efforts to reduce the incidence of hypertension in the elderly: A literature review - Rumatrai, Jein Dini F; Gurning, Maylar; Mannopposem, Inggerid A (Indonesian Journal of Health Services, 2024)
Hypertension is a major public health problem among elderly populations and contributes significantly to cardiovascular morbidity and mortality worldwide. Lifestyle modification, particularly physical activity, plays an important role in preventing and managing hypertension in older adults. Objective: This study aimed to examine the effect of physical activity in efforts to reduce the incidence of hypertension in the elderly through a literature review approach. Methods: This study employed a literature review design following the PRISMA guideline. Articles were searched through the Google Scholar database using the keywords physical activity, hypertension, and elderly. The search was limited to articles published between January 2020 and December 2024. Eligible studies included research articles that examined physical activity interventions aimed at reducing blood pressure among elderly populations. Ten relevant studies were selected after applying inclusion and exclusion criteria. Data were extracted and synthesized using a narrative analysis approach. Results: The review identified various physical activity interventions including structured walking programs, hypertension exercise, ergonomic exercise, and Buerger-Allen exercise. Most interventions were conducted for three to eight weeks and demonstrated reductions in systolic blood pressure ranging from approximately 5–15 mmHg. Several complementary therapies such as relaxation techniques also contributed to blood pressure reduction. The findings indicate that regular physical activity improves cardiovascular regulation, enhances physical fitness, and supports better hypertension control among elderly individuals. Conclusion: Physical activity interventions provide effective non-pharmacological strategies for reducing blood pressure among elderly populations. Integrating structured physical activity programs into community health services can strengthen hypertension prevention and promote healthy aging.